Pass it on : African-American Poetry for Children - Wade Hudson (United Kingdom Scholastic Press, 1993)
A collection of poetry by fourteen distinguished African-American poets features the work of Langston Hughes, Paul Laurence Dunbar, Gwendolyn Brooks, and Eloise Greenfield, among others.
Keywords: Poetry -- Read Aloud